Shaping the public sphere with and beyond the state - Berger, Dan (Javnost (Ljubljana), 2006)
This paper argues that public opinion theory has been guided by a confused, arguably contradictory relationship between the public and the state. Guided by an elitist view toward the masses, traditional theories argue that the public takes place only in opposition to the state yet cannot be trusted to run society on its own. Such a normative ideal, while perhaps inherently troubling, is more irrelevant in a world defined by globalisation. In particular, several social movements and governments in Latin America offer analternate approach to conceptualising the relationship between the public and the state - a model whereby the two work in tandem to run society. Such moves, critically examined here, are particularly fueled by neoliberal economic policies.
Keywords: javna sfera; javnost; država; state; democracy; demokracija; družbena gibanja; odnosi z javnostmi; javno mnenje